(3LeY eG GfJTQ ef CNHGQ NjQ GdHTQs - (3CHh YHO Gddg SjOj eMeO Hf ehdGj GOQjS GdYQGbj GdMSjfj,J (B1142 (3g` s
(3ChdgG (B:s
[(3hHYO(B] (3agPG LeY eG GfJTQ ef CNGQ NjQ GdHTQ ,aUOJJ Hg Ydi SHjd GdETgGQ ,hJbdjd GdHMK hSdhc GdGbJUGQ s
(3BNQgG (B:s
(3cPG bjd ,hOdjd LhGRgG Ydi GdCfHjGA QhGjI GdHjgbi hZjQg Yf CHj gQjQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B16s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B141 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(43 (3c(B) s
Keywords: (3GdJGQjNs